Analisis Simpanan Deposito Mudharabah Pada PT Bank Syariah Indonesia Kantor Cabang Pembantu Stabat - Liyan Sari; Muhizar Muchtar; Rani Febriyanni (Al-Sharf: Jurnal Ekonomi Islam, 2022)
The purpose of this study is to analyze mudharabah deposit deposits at PT Bank Syariah Indonesia Stabat Auxiliary Branch Office. This research is a type of qualitative research using a descriptive approach through field studies (field research) by making observations at the research site. Then continued by conducting interviews and document research and documentation to then make conclusions. The results showed that based on the results of interviews conducted with the head of Bank Syariah Indonesia KCP Stabat obtained information that The Indoesia KCP Stabat Sharia bank has several products and the most in demand are savings products with mudharabah and wadiah systems. Deposit deposits with the principle of mudharabah are quite in demand by the people in Langkat Regency who save at the Indonesian Islamic bank KCP Stabat because it is mutually beneficial and free from the element of riba prohibited by religion. Bank Syariah Indonesia KCP Stabat's mudharabah deposit system already uses the ARO (automatic roll over) system, meaning that deposits will be automatically extended by the bank without having to confirm to the holder of term deposits. Customers do not need to come to the office to extend the deposit period.